Evaluating CMIP5 ocean biogeochemistry and Southern Ocean carbon uptake using atmospheric potential oxygen: Present‐day performance and future projection. Issue 5 (5th March 2016) - Nevison, C. D.; Manizza, M.; Keeling, R. F.; Stephens, B. B.; Bent, J. D.; Dunne, J.; Ilyina, T.; Long, M.; Resplandy, L.; Tjiputra, J.; Yukimoto, S.
Abstract: Observed seasonal cycles in atmospheric potential oxygen (APO ~ O2  + 1.1 CO2 ) were used to evaluate eight ocean biogeochemistry models from the Coupled Model Intercomparison Project (CMIP5). Model APO seasonal cycles were computed from the CMIP5 air‐sea O2 and CO2 fluxes and compared to observations at three Southern Hemisphere monitoring sites. Four of the models captured either the observed APO seasonal amplitude or phasing relatively well, while the other four did not. Many models had an unrealistic seasonal phasing or amplitude of the CO2 flux, which in turn influenced APO. By 2100 under RCP8.5, the models projected little change in the O2 component of APO but large changes in the seasonality of the CO2 component associated with ocean acidification. The models with poorer performance on present‐day APO tended to project larger net carbon uptake in the Southern Ocean, both today and in 2100. Key Points: Seasonal cycles in atmospheric potential oxygen (APO) are useful for evaluating ocean models CMIP5 models show clear differences in their skill at reproducing observed APO seasonal cycles CMIP5 models that perform poorly on APO tend to project a larger future Southern Ocean carbon sink